Peningkatan Wawasan Kepemimpinan dan Manajemen bagi Siswa SMA Negeri 2 Babat Toman - Ellisyah Mindari (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2022)
Students in Indonesia's youth generation, which is leading positive change, have the chance to grow in self-awareness and become individuals of integrity and quality. Participants who can think critically about all disputes are pioneers and turning points in social development and change as change agents and social control agents. In order to convey the understanding of leadership and management to students who have established managerial abilities, are creative, and are able to manage the organization, training in leadership and management from the very beginning as a manifestation of future national leadership needs to be updated as the first stage of construction. Head of LPPM STIE Rahmaniyah Sekayu and Principal of Senior High School 2nd Babat Toman are working together on this project. The dedicated method involves lectures, seminars, and case studies while also putting the ideas of management and leadership into practice. According to the higher post-test values compared to the pre-test values obtained by the participants before the activity took place, it can be said that this community service project was successful because it caused the participants to increase their observation of leadership and management.